Pengaruh Gaya Hidup Dan Perilaku Konsumtif Terhadap Keputusan Pembelian Produk Menggunakan Aplikasi E Money â€œ Shopee Pay â€ Pada Mahasiswa Universitas PGRI Madiun - Kevin Prasetya Aditya Putra; Wikanso Wikanso; Yahya Reka Wirawan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to: (1) determine the effect of lifestyle on product purchase decisions using the e-money application "shopee pay", (2) determine the effect of consumptive behavior on product purchase decisions using the e-money application "shopee pay", (3) determine the effect lifestyle and consumptive behavior on product purchasing decisions using the e-money application "Shopee Pay". This research method is included in quantitative research with associative causal research. As for data collection techniques using questionnaires and documentation. The sampling technique used is random sampling. The population in this study is PGRI Madiun University students who use the "shopee pay" e-money application. The sample in this study was 126 respondents. Data were analyzed using SPSS version 26 which showed that variable X1 had a significant effect of 52.3% partially. While the variable X2 has a significant effect of 6.8% partially. While the rest is influenced by other factors not explained in this study.